Application of the Fun Learning Model in Improving Poetry Writing Skills of Students - Aliem Bahri (Studies in Learning and Teaching, 2023)
The main problem is the low skill of writing poetry in class V students at Unismuh Elementary School, Makassar City. This study aims to apply the fun learning model to improve poetry writing skills in fifth grade students at Unismuh Elementary School, Makassar City. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is held in four meetings. Research procedures include planning, implementation of action, observation, and reflection. The research subjects were 25 class V students. The collected data were analyzed using quantitative and qualitative analysis. The results of this study are the acquisition of an average score of students' learning outcomes in the first cycle of 60.7 while in the second cycle, the average score of students' learning outcomes has increased to 85.5 which is in the high category. Mastery learning to write poetry in cycle I, 24% of students achieved learning mastery, while in cycle II as much as 92%. In cycle II there was an increase in learning activities and writing poetry compared to cycle I. The novelty of the research is that fun learning not only improves learning activities, learning outcomes but also poetry writing skills in students.